Contrast induced nephropathy by interventionist cardiology - Dra. Xiomara Castelo Villalón; Dra. Yudmila Reina Borges Moreno; Dra. Grisel Guevara Mirabal; Dra. Anneris Martínez Carrillo; Dra. Sheila Hechavarría Pouymiro; Lic. Jilka Lietys García Romero (ECIMED, 2017)
Introduction: The damage of kidney function due to the use of contrast agents (nephropathy induced by contrast agents) has been increased in the last years because of a higher number of interventionist procedures has been performance in patients with cardiovascular or another diseases. Nephropathy induced by contrast agents is reversible, but it could delay permanency in the hospital of these patients, besides in those with high risk of kidney dysfunction, the damage could be irreversible. In the Institute of Cardiology and cardiovascular surgery carry out annually an average of 1533 interventional procedure that's why we feel motivate to realize this medical review. Objective: To deepen in the study of nephropathy induced by contrast agents. Develop: We reviewed articles aboilables in the past 10 years related with this topic. Then we analyzed and summarized this information. Conclusions: The progressive increased of diagnostics and therapeutics procedures, using intravenous contrast agents in cardiology are related to a high morbility such as kidney dysfunction due to nephropathy induced by contrast agents.